READING UP THE VERSE PATTERN OF ELIZABETH BARRETT BROWNINGÃ¢â¬â¢S HOW DO I LOVE THEE? - Ariya Jati (TEFLIN, 2007)
Reading a poem is systematic, distinctive and patterned. Written as a sonnet, How do I Love Thee? is akin to neither Shakespearean nor Petrarchan sonnet. The verse pattern of the sonnet is typical: it is composed of two quatrains and one sestet, rhyming in abba abba ababab. Each iambic pentameter line of the sonnet is isochronous. The alliteration and assonance associate the words deployed to express the greatness of Elizabeth Barrett BrowningÃ¢â¬â¢s feeling of love.